Legal Policy of Child Marriage In the Covid-19 Pandemic Period - Subchi, Imam; Arsadani, Qosim; Helmi, Muhammad Ishar; Faridho, Efin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
The increase in marriage dispensation applications that occurred during the Covid-19 pandemic also caused the high number of child marriage. Nevertheless, this has been strictly required in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage (Marital Law), the minimum age limit for men and women is 19 years, and requirements of irregularities for this age that must meet urgent criteria and sufficient support evidence. This is done, to reduce underage child marriages as a form of enforcing the principle of children's best interests. This paper describes the complexity of underage children's marriage during the Covid-19 pandemic period, as a convenience requirement of marriage dispensation has been set rigid in the Marriage act. The method used in this paper is normative by using several approaches: the statute approach, conceptual approach, and case approach. The results of the government's policy during the Covid-19 pandemic period which brought massive changes to the community's order had an impact on the collapse of the family economy. This resulted in the mass number of the child's marriages in the pandemic period. The research findings of this study deliver to children's rights violations through child marriages. The risk of decreasing individual economies, maternal and infant health, and household violence become unavoidable considering the psychological conditions of children who are immature in marriage.